Target Strength Identification Using Commercial Echo Sounder - Sunardi, S.; Norzirwatul Ahlam, Naharuddin; Elmis Salinas, Mad Sariff (2014)
This research proposes the acoustic measurement by using commercial echo sounder JMCV1082 model to detect the object underwater. The acoustic scattering is depends on shape, size, and material properties An envelope echo signal produced using 50 IU-Iz and 200 KHz echo sounder receiver. Various spheres and cylinder are used in this experiment. Cylinder is used for detection of diver underwater. The transducer was positioned about 1, 2, 3, 4, 5 meter from the target (sphere and air-filled). The commercial echo sounder was modified to obtain the echo/output signal from transducer and transmit the signal through high speed analog input USB to be record and analyze using a computer or laptop. MATLAB software was used to analyze the output/echo signal of the commercial echo sounder and the echo observation is in time and frequency domain. The modification of signal output presentation is needed for target strength identification. The target strength of object is depends on size of the object. The bigger size of object will have bigger target strength value. Although the structure signal without any object are different compare to the signal from the object, the reflected signal from the tank floor increase linearly with the object size.